LIGHT OF THE STARS ALIEN WORLDS AND THE FATE OF THE EARTH - ADAM FRANK (NEW YORK W W NORTON & COMPANY, 2018)
Astrophysicist and NPR commentator Adam Frank reveals what the latest research on alien civilisations may tell us about our own.
Keywords: COSMOLOGY -- EXOBIOLOGY